Teachers’ Strategies in Instilling Religious and Disciplinary Character Values - Supriyandi, Reno; Chandra, Pasma; Marhayati, Nelly (Jurnal Pendidikan Islam, 2025)
Character education has become a central concern in the development of quality human resources, particularly in Islamic educational institutions where the integration of religious and disciplinary values is essential. However, the effectiveness of strategies implemented by teachers in cultivating these values often faces challenges related to students’ diverse backgrounds, the boarding school environment, and institutional resources. This study aims to analyze the strategies implemented by Islamic Religious Education (PAI) teachers in cultivating religious and disciplinary character values of class XI students at MAN Insan Cendekia Bengkulu Tengah, as well as identifying factors that influence the implementation of these strategies. This type of research uses a qualitative approach with the methods of in-depth interviews, participatory observation, and documentation studies, this research examines the holistic and integrated practice of character education in a boarding school environment. The results showed that PAI teachers implement various strategies that are mutually sustainable. To cultivate religious character, the strategies include scheduling and special attendance of worship practices, utilization of educational rules and sanctions, giving additional practice tasks, intensive coaching in the dormitory, exemplary PAI teachers (uswatun hasanah), and utilization of learning media and technology. Meanwhile, to cultivate the character of discipline, PAI teachers implemented the enforcement of school rules and regulations, the provision of sanctions and rewards, supervision and guidance in the dormitory, and the implementation of the parenting program. The implementation of these strategies is influenced by various factors, both supporting and inhibiting. Supporting factors include active support from parents, competence and professionalism of PAI teachers, conducive school environment, availability of adequate facilities and infrastructure, and students’ intrinsic motivation and awareness.